TI_GERICHTE 52.2009.490 vom 29. August 2013 , Distribuzione dell'acqua potabile assicurata da una degagna: parità di trattamento - TI Tribunale d'appello (2013)
Distribuzione dell'acqua potabile assicurata da una degagna: parità di trattamento